2023
DOI: 10.1126/sciimmunol.abq0375
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of VEGFR3 signaling leads to functional impairment of dural lymphatic vessels without affecting autoimmune neuroinflammation

Abstract: The recent discovery of lymphatic vessels (LVs) in the dura mater, the outermost layer of meninges around the central nervous system (CNS), has opened a possibility for the development of alternative therapeutics for CNS disorders. The vascular endothelial growth factor C (VEGF-C)/VEGF receptor 3 (VEGFR3) signaling pathway is essential for the development and maintenance of dural LVs. However, its significance in mediating dural lymphatic function in CNS autoimmunity is unclear. We show that inhibition of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 73 publications
1
24
0
Order By: Relevance
“…All of these populations participate in changes in the ECM during infection, including collagen and proteoglycan deposition and regulation of the ECM, highlighting the extensive ECM remodelling taking place in the meninges during chronic infection. The ontogeny of the meningeal FDC-like cells that we detected under chronic infection with T. brucei, and whether they play an active role in the neuroinflammatory process in this infection setting 86 , requires further investigation. Nevertheless, to our knowledge, this is the first report characterising the response of meningeal fibroblasts to chronic infections with a protozoan parasite, which has important implications for understanding how dynamic and adaptable the meningeal stroma is under chronic inflammatory processes.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…All of these populations participate in changes in the ECM during infection, including collagen and proteoglycan deposition and regulation of the ECM, highlighting the extensive ECM remodelling taking place in the meninges during chronic infection. The ontogeny of the meningeal FDC-like cells that we detected under chronic infection with T. brucei, and whether they play an active role in the neuroinflammatory process in this infection setting 86 , requires further investigation. Nevertheless, to our knowledge, this is the first report characterising the response of meningeal fibroblasts to chronic infections with a protozoan parasite, which has important implications for understanding how dynamic and adaptable the meningeal stroma is under chronic inflammatory processes.…”
Section: Discussionmentioning
confidence: 96%
“…The ontogeny of the meningeal FDC-like cells that we detected under chronic infection with T. brucei, and whether they play an active role in the neuroinflammatory process in this infection setting 73 requires further examination. Nevertheless, to our knowledge, this is the first report characterising the dynamics of meningeal fibroblasts to chronic infections with a protozoan parasite, which have important implications for understanding how dynamic and adaptable the meningeal stroma is under chronic inflammatory processes.…”
Section: Discussionmentioning
confidence: 98%
“…Altogether, these data might suggest that brain-to-CLN signaling is responsible for triggering systemic inflammatory responses after acute stroke 13 . However, another study using a mouse model of the active experimental autoimmune encephalomyelitis (EAE) shows that VEGFR3 blockade in mice induced dural lymphatic vessel impairment and was insufficient to block autoimmune neuroinflammation 102 , implicating that lymphatic inflammation can have complex double-edged sword actions of either one can worsen acute tissue damage, or under some conditions the other mechanism can also help resolve damage and promote repair 103 , 104 .…”
Section: Pathological Relevance Of Brain To Cln Connectionmentioning
confidence: 99%
“…does not significantly contribute to progressing autoimmune neuroinflammation (Li et al, 2023). Therefore, in-depth basic research is needed to determine the molecular mechanisms of epilepsy and to measure the strengths and weaknesses of Vegfc as a therapeutic agent.…”
Section: Findingmentioning
confidence: 99%
“…However, such treatment may also lead to MLV degeneration, altering CSF and ISF homeostasis and affecting neurological function and immunity (Blanchette & Daneman, 2017). Although a recent study has shown that inhibiting Vegfc/Vegfr3 does not significantly contribute to progressing autoimmune neuroinflammation (Li et al., 2023). Therefore, in‐depth basic research is needed to determine the molecular mechanisms of epilepsy and to measure the strengths and weaknesses of Vegfc as a therapeutic agent.…”
Section: Potential Option For Epilepsy Treatment Based On Cerebral Ly...mentioning
confidence: 99%